2014
DOI: 10.4049/jimmunol.1303030
|View full text |Cite
|
Sign up to set email alerts
|

Provirus Activation Plus CD59 Blockage Triggers Antibody-Dependent Complement-Mediated Lysis of Latently HIV-1–Infected Cells

Abstract: Latently HIV-1-infected cells are recognized as the last barrier towards viral eradication and cure. To purge these cells, we combined a provirus stimulant with a blocker of human CD59, a key member of the regulators of complement activation (RCA), to trigger antibody-dependent complement-mediated lysis (ADCML). Provirus stimulants including prostratin and histone deacetylase inhibitors (HDACi) such as romidepsin (RMD) and suberoylanilide hydroxamic acid (SAHA) activated proviruses in the latently HIV-1-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 79 publications
(98 reference statements)
4
33
0
Order By: Relevance
“…However, accumulating data sug-gest that short-term or transient blockage of CD59 may be feasible and tolerable to HIV-1 patients, since CD59 blockage, deficiency, or knockout does not cause severe off-target effects in vitro and in vivo (72)(73)(74)(75)(76)(77)(78)(79)(80). We and others have demonstrated that the use of CD59 blockers in vitro to block CD59 does not cause nonspecific cytolytic effect on cell lines, human RBCs, or PBMCs in the presence of sera/plasma from HIV-1-infected patients (33)(34)(35). Thus, CD59 blockers that are expected to be used short term, not lifelong, will be better tolerated in HIV-1 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, accumulating data sug-gest that short-term or transient blockage of CD59 may be feasible and tolerable to HIV-1 patients, since CD59 blockage, deficiency, or knockout does not cause severe off-target effects in vitro and in vivo (72)(73)(74)(75)(76)(77)(78)(79)(80). We and others have demonstrated that the use of CD59 blockers in vitro to block CD59 does not cause nonspecific cytolytic effect on cell lines, human RBCs, or PBMCs in the presence of sera/plasma from HIV-1-infected patients (33)(34)(35). Thus, CD59 blockers that are expected to be used short term, not lifelong, will be better tolerated in HIV-1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Blockage of hCD59 function with intact BRIC229 molecules allows anti-HIV-1 gp120/gp160 Abs or Abs in the sera/plasma from HIV-1-infected individuals to restore their activity of ADCML to destroy complement-resistant HIV-1 virions and infected cells (30)(31)(32)(33)(34). We have recently reported that blockage of hCD59 renders provirus-activated ACH-2 cells and primary human CD4 ϩ T cells that were latently infected with HIV-1 sensitive to ADCML by anti-HIV-1 polyclonal Abs or plasma from HIV-1-infected patients (35). However, it is unclear whether F(ab=) 2 fragments of BRIC229 would retain hCD59-blocking activity of the intact Ab of BRIC229.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While several studies have utilized latently infected cell lines to examine reactivation of the latent provirus (39,40) and even elimination of reactivated cells (41), transformed cell lines may not be ideal models of HIV-1 latency and may not be reflective of primary CD4 ϩ T cells as targets for ADCC. Latently infected CD4 ϩ T cells are rare in HIV-1 ϩ subjects on ART (approximately 1 replication-competent virus per million resting CD4 ϩ T cells [38]), and to obtain sufficient HIV-1-infected CD4 ϩ T cell targets, it was necessary to activate the primary cells with mitogens and culture them for several days.…”
Section: Discussionmentioning
confidence: 99%